The Rhetoric of Kalam Insya’i in Allah’s Commands and Warnings in Surah At-Tahrim: A Stylistic Analysis of Qur’anic Language - Khairunnisa, Naura Maulika; Laili, Nur; Zahro, Mahdiya Intan (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Rhetoric in the Qur’an is a communicative strategy used to convey divine messages both explicitly and implicitly, in order to reinforce the meaning contained within the text. One form of rhetoric in the Qur’an is kalam insya’i, which includes interrogative (istifham), command (‘amr), prohibition (nahy), vocative (nidā’), wishful expression (tamanni), exclamation (ta‘ajjub), praise and criticism (al-madh wa al-dhamm), oath (al-qasam), and hope (rajā’). Surah At-Tahrim, one of the madaniyah surahs, meaning "prohibition", is dominated by Allah’s commands and warnings directed to His servants. This study aims to uncover the commands and warnings of Allah in Surah At-Tahrim and the embedded messages conveyed through an analysis of the rhetoric of kalam insya’i. The research method employed is descriptive qualitative, using an Arabic stylistic approach. The primary source is Surah At-Tahrim, while secondary sources consist of related articles on stylistic analysis and studies concerning the surah. The data analysis process includes stages of data collection, selection, and in-depth analysis. Preliminary findings show that there are three commands and three warnings conveyed by Allah in Surah At-Tahrim. The use of assertive language with profound meaning creates a strong emotional impact on the reader, effectively stirring the soul and conveying the divine message hidden within the text.